FRI0180 Higher likelihood of response in rheumatoid arthritis patients treated in a real-life setting with adalimumab in combination with methotrexate, but not with other dmards, versus adalimumab monotherapy. (23rd January 2014) - Kiely, P.; Florentinus, S.; Keidel, S.; Lacerda, A.; Karunaratne, M.; McCaskill, R.
Abstract : Background: Clinical trial data support the superiority of combining adalimumab (ADA) with DMARD(s) vs ADA alone. The use and effectiveness of ADA + DMARD(s) over monotherapy require confirmation in real-life settings. Objectives: To compare the use and response of ADA taken with or without DMARD(s) in a real-life setting. Methods: Biologic-naïve rheumatoid arthritis (RA) patients (pts) registered through the BSRBR (Sep '02-Mar '10) who received their 1 st ADA dose were followed for 6 months. At enrollment, pts required a DAS28 >5.1 and ≥2 DMARD failures. Pts were categorized by baseline DMARD use: combination therapy without MTX (non-MTX DMARD), with MTX (MTX DMARD), and ADA monotherapy. Clinical and functional responses were assessed as the proportions achieving 1) clinically meaningful reductions from baseline (Δ) in DAS28 (>1.2) and HAQ (>0.22), respectively, or 2) the more stringent targets, DAS28 <3.2 and HAQ <0.5, respectively. Logistic regression modeled the odds of response for the non-MTX DMARD and MTX DMARD groups relative to ADA monotherapy, following adjustment for baseline differences. Results: Of 4470 pts initiating ADA, 3123 (70%) received ≥1 DMARD (727 non-MTX DMARD, 2396 MTX DMARD) and 1347 (30%) received ADA monotherapy. At month 6, mean DAS28 and HAQ improved in all 3 groups (Table ), with the greatest improvements observed for pts receiving MTX. There was a significantly higher likelihood of achieving ΔDAS28 >1.2, DAS28 <3.2, and ΔHAQ >0.22 in the MTX DMARD group compared with ADA monotherapy, with a trend for the non-MTX DMARD group. A trend for a higher likelihood of achieving HAQ <0.5 was observed in both DMARD groups. Conclusions: In this cohort with severe RA, ADA improved overall disease activity and function at 6 months, both as monotherapy and in combination with DMARD(s). Combining ADA with MTX, but not with other DMARDs, appeared to increase the likelihood of response vs monotherapy in this real-life setting. Acknowledgements: AbbVie Inc. is a co-sponsor of the BSRBR. AbbVie Inc. participated in the analysis and interpretation of the data, and in the writing, reviewing, and approval of the final version of the abstract. Medical writing support was provided by Benjamin Wolfe, PhD, of AbbVie Inc. Disclosure of Interest: P. Kiely Consultant for: AbbVie Inc., BMS, MSD, UCB, Pfizer, Roche, Savient, S. Florentinus Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., S. Keidel Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., A. Lacerda Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., M. Karunaratne Shareholder of: AbbVie Inc., Employee of: AbbVie Inc., R. McCaskill Shareholder of: AbbVie Inc., Employee of: AbbVie Inc.